2021
DOI: 10.3389/fpubh.2021.592795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on Physical Activity Among the Chinese Youths: The COVID-19 Impact on Lifestyle Change Survey (COINLICS)

Abstract: Background: The study sought to assess the changes in physical activity (PA) and sedentary time among Chinese youths at different stages after the COVID-19 outbreak.Methods: It was based on a retrospective online survey conducted in May 2020. More than 10,000 youths voluntarily recalled their PA-related information at three stages: before COVID-19 (January), during lockdown (February), and after lockdown (May). χ2 tests were conducted to evaluate the significance of the differences in participants' characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…First, since our study measures a before and after scenario by asking about the "before" retrospectively and the social capital data are self-reported, there may be recall and reporting bias; particularly, this recall was made during a traumatic ongoing event, which may further skew the perception of all levels of social capital (e.g., being underperceived) due to negative or depressive emotion during the long-lasting pandemic. However, the self-assessment of social capital at two time points might reflect their perceived changes which are usually closely correlated with their actual changes (16,25,26). Second, we only measured two time points in this study, thus were not able to track the dynamic trends of social capital during the whole period (27).…”
Section: Discussionmentioning
confidence: 96%
“…First, since our study measures a before and after scenario by asking about the "before" retrospectively and the social capital data are self-reported, there may be recall and reporting bias; particularly, this recall was made during a traumatic ongoing event, which may further skew the perception of all levels of social capital (e.g., being underperceived) due to negative or depressive emotion during the long-lasting pandemic. However, the self-assessment of social capital at two time points might reflect their perceived changes which are usually closely correlated with their actual changes (16,25,26). Second, we only measured two time points in this study, thus were not able to track the dynamic trends of social capital during the whole period (27).…”
Section: Discussionmentioning
confidence: 96%
“…8,9 Despite the potential benefits of physical activity on child well-being, emergent data suggest that during this pandemic, access to health-promoting physical activity has been largely disrupted, whereas use of screen-based media for education and recreation has increased. [10][11][12] Studies from before the pandemic indicate that only 24% of US children and adolescents aged 6 to 17 years met recommendations for 60 minutes per day of physical activity. 4 Data from the 2017 National Youth Risk Behavior Survey showed that 26.1% of high school students had been physically active for a total of at least 60 min/d on all 7 days before the survey.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, China as the first country to be affected by COVID-19 and also the first to implement and lift the blockade measures provides valuable evidence and references to other countries. The study of Zhou et al (2021), using a large sample of young Chinese, found that COVID-19 had a significant and adverse effect on young people's physical activity and sedentary posture, and such effects persisted for at least 3 months. Specifically, physical activity was significantly reduced, but sitting time was significantly increased during the blockage (Zhou et al 2021).…”
Section: Discussionmentioning
confidence: 99%